Networking in E-textiles - Nakad, Z. (2010)
The abundance of fabrics in our life offers immense possibilities for ubiquitous electronic integration. Electronic textiles (e-textiles) represent the merging of fabric and electronic technologies to be used in wearable and large-scale applications. The communication requirements of the computing elements of these systems will be presented along with a fault tolerant solution. The operation of the communication scheme will be studied analytically and compared to simulation results. The graceful deterioration of the performance with increasing faults will also be reported. Multiple e-textile application examples utilizing the networking scheme will be presented.